PENDAMPINGAN PENGELOLAAN KEUANGAN DAN PENYUSUNAN LAPORAN KEUANGAN BERBASIS ANDROID PADA UMKM KELURAHAN MANGUNHARJO KECAMATAN TEMBALANG KOTA SEMARANG - Hendri Setyawan; Chrisna Suhendi (Universitas Majalengka, 2021)
Despite its large contribution to the economy, MSMEs players face various problems, including access to capital, poor financial management and the absence of an adequate medium and long term financial management strategy. This community service is carried out with the general objective of empowering Micro, Small and Medium Enterprises to be able to survive and develop with their own uniqueness. The specific objectives of this activity are for the target MSMEs to have adequate financial management and for the target MSMEs to be able to prepare simple financial reports. The existence of a pandemic has made mentoring activities carried out online with a zoom platform. Financial management assistance is provided by providing some knowledge / skills related to financial management, especially during times of crisis. The accounting system used uses a mobile application platform in collaboration with the Indonesian Institute of Accountants which is available for free at the appstore, namely Si Apik. Activities of assistance in financial management and preparation of android-based financial reports for MSMEs are very beneficial. Assistance activities are very useful and practical for MSME entrepreneurs. Assistance needs to be carried out continuously to instill a good accounting and financial mindset in the management of MSME business finances.